Effect of Nano Chitosan Concentration and Storage Temperature on the Physical Characteristics of Edible Films of Black Mangrove Starch-Chitosan - Mile, Lukman; Nursyam, Happy; Setijawati, Dwi; Sulistiyati , Titik Dwi (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Edible films made from chitosan and starch materials have several physical limitations, particularly in terms of tensile strength and elongation. To address these limitations, glycerol and sorbitol are often added as plasticizers during the production process. Chitosan has also been reported to have plasticizing properties and can serve as an alternative through its modification into nano-sized particles, thereby increasing its reactivity. Therefore, this study aimed to characterize the physical properties of edible films made from black mangrove (Rhizophora mucronata) fruit starch and chitosan by adding nano chitosan suspension at different storage temperatures to determine the best treatment. A completely randomized factorial design was used, and the data obtained were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level with IBM SPSS statistics 25. The treatments used included the addition of nano chitosan suspension (A) at various concentrations of 0%, 25%, 50%, and 75% with storage (B) for 0 days, 9 days at room temperature, and 9 days at cold storage (± 50C) in triplicates. The significant treatments were then further tested using Honestly Significant Difference (sig < 0.05). The results showed that the addition of nano chitosan suspension with storage method affected the physical properties of the edible films. The edible film made from black mangrove fruit starch-chitosan with the addition of nano chitosan (50%:50%:75%) stored at cold temperature for 9 days had the best physical properties to be applied as a package for fishery products (fillets) based on De Garmo analysis.   Highlight Research Nano chitosan can be applied as plasticizer in making edible film of black mangrove starch-chitosan. The concentration of nano chitosan and storage temperature influenced the thickness, tensile strength, elongation, young modulus, and water resistance of edible film. The edible film made from Black mangrove starch - chitosan with the addition of 75% concentration of nano chitosan when stored at cold temperature (5 0C) for nine days can increase tensile strength, young modulus, elongation, and water resistance. Components of edible films interact less with one another intermolecularly due to nano chitosan, which encourages the creation of hydrogen bonds between polymer chains.